2007
DOI: 10.1007/s10147-007-0691-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mass-like consolidation after stereotactic body radiation therapy for lung tumors

Abstract: Mass-like consolidations were observed in 68% of cases at a median of 5 months after SBRT. Although most of the mass-like consolidations were RILI, local recurrence was observed in a few cases. Early detection of local recurrence after SBRT was difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 17 publications
(14 reference statements)
4
46
0
Order By: Relevance
“…36,37 In addition, due to its retrospective nature and the relatively short FU, it cannot be excluded that some findings are biased with patient selection and that some structural changes may theoretically occur later, since the fibrotic evolution after high-dose irradiation is a dynamic process that might continue for many years. 38,39 A further limitation is that the scoring of CT changes after lung HHT adopted herein 23,24 is qualitative and may be subjective. Alternative methods, such as the use of CT density changes, may represent an objective measure of lung damage because density changes strongly correlate with histological findings of inflammation, 40 thus allowing for a more robust dose-response relationship based on quantitative data.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In addition, due to its retrospective nature and the relatively short FU, it cannot be excluded that some findings are biased with patient selection and that some structural changes may theoretically occur later, since the fibrotic evolution after high-dose irradiation is a dynamic process that might continue for many years. 38,39 A further limitation is that the scoring of CT changes after lung HHT adopted herein 23,24 is qualitative and may be subjective. Alternative methods, such as the use of CT density changes, may represent an objective measure of lung damage because density changes strongly correlate with histological findings of inflammation, 40 thus allowing for a more robust dose-response relationship based on quantitative data.…”
Section: Discussionmentioning
confidence: 99%
“…As for SRBT, RFA causes focal lung changes such as ground glass opacities surrounding the tumour [46]. This represents a transition from the ablated area to a reactive pneumonia in the nearby normal lung tissue [40]; it also represents a "safety boundary": a ground-glass margin of 5 mm or more, is reported to indicate full ablation [47] (Fig. 5).…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 97%
“…Detection of recurrence may be difficult within 9 months of the delivery of SBRT because of secondary radiation pneumonitis [39]. Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence. Otherwise, other findings already described as signs of recurrence after conventional radiotherapy can be used to suspect recurrence after SBRT; these include the filling of radiation-induced ectatic bronchi [41], development of bulging at margins of radiation-induced consolidation, and [39].…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 98%
“…One classification system describes four patterns of RILI, namely the modified conventional, mass-like and scar-like fibrosis as well as the "no evidence of increased density" pattern (5). Mass-like fibrosis, defined as a "well-circumscribed focal consolidation limited to area surrounding the tumor and the abnormality must be larger than the original tumor" (5) is a particularly challenging form of RILI to distinguish from local recurrence (5,8,9) and leads to clinical concerns relating to whether the changes are suspicious and what, if any, interventions are appropriate (9,10). However, the majority of cases of mass-like fibrosis remain stable over time without development of recurrence, and are thus confirmed as RILI.…”
mentioning
confidence: 99%